2022
DOI: 10.1148/radiol.211288
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Late Contrast Enhancement CT in Troponin-Positive Acute Chest Pain Syndrome

Abstract: cute chest pain or anginal equivalents associated with mild troponin rise remain a diagnostic challenge, particularly in patients at low to intermediate risk for acute coronary syndrome. Coronary CT angiography can be used to safely triage these patients (1,2). In previous large multicenter trials with participants with acute chest pain at low to intermediate pretest risk of acute coronary syndrome, coronary CT angiography was associated with higher detection of coronary artery disease (CAD) (3), shorter lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 35 publications
0
35
0
1
Order By: Relevance
“…However, Stefanini et al found out that 39% of COVID-19 patients with STEMI had negative invasive coronary angiography (ICA) probably for the higher prevalence of type-2 MI in patients during the acute phase of COVID-19. These data further supported the use of CCTA in COVID-19 patients [47], also having the advantage to simultaneously rule-out coronary artery disease (CAD) and pulmonary embolism (PE) using a triple rule-out scanning protocol [23,24] and to refine risk stratification of COVID-19 patients with the quantification of coronary artery calcium score (CAC) [7,9,10,16,25,48].…”
Section: Cardiac Imaging In Covid-19mentioning
confidence: 69%
See 2 more Smart Citations
“…However, Stefanini et al found out that 39% of COVID-19 patients with STEMI had negative invasive coronary angiography (ICA) probably for the higher prevalence of type-2 MI in patients during the acute phase of COVID-19. These data further supported the use of CCTA in COVID-19 patients [47], also having the advantage to simultaneously rule-out coronary artery disease (CAD) and pulmonary embolism (PE) using a triple rule-out scanning protocol [23,24] and to refine risk stratification of COVID-19 patients with the quantification of coronary artery calcium score (CAC) [7,9,10,16,25,48].…”
Section: Cardiac Imaging In Covid-19mentioning
confidence: 69%
“…CT assessment offers the additional advantage of COVID-19 pneumonia severity assessment [1] and to reveal subclinical CV risk factors such as liver steatosis [49], myosteatosis [50], and epicardial fat volume and attenuation [11,51]. Finally, CT may offer the opportunity to characterize myocardial scar and extracellular volume fraction (ECV) with the addition of a late contrast enhancement scan [23,24,52,53]. This may be particularly useful and effective especially in the emergency setting [23], providing a full range of diagnosis with a single examination requiring few minutes, without the need of CMR [24] (Fig.…”
Section: Cardiac Imaging In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, CT (computed tomography) is increasingly enumerated beside MRI as an alternative imaging tool for estimation of myocardial oedema or myocardial fibrosis, particularly in those with contraindications to the latter. Several studies have demonstrated that, similarly to MRI, in CT imaging the late contrast enhancement may visualise the difference between the normal and damaged myocardium [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Both diseases might be presented with increased levels of cardiac serum enzymes and inflammatory biomarkers [4,32,33]. However, a TnT level within normal limits does not exclude the diagnosis of myocarditis but may constitute a prognostic factor of a better outcome [27,34,35]. Serum cardiac biomarkers are routinely measured in patients presenting with chest pain in ED.…”
Section: Discussionmentioning
confidence: 99%